Firms’ Profitability and Stock Returns: Does it Always Affect Positively? - Budi, Hananiel Stephen Mangku; Davianti, Arthik (International Journal of Social Science and Business, 2022)
Stocks reflect a company’s owner proof, which means that every investor expects the maximum returns from the cost incurred when buying stocks. Previous research stated that profitability has a positive relationship with stock returns. Meaning that a highly profitable company will increase the company values, and eventually, the stock prices will increase. However, the Indonesia Consumer Goods Industry Index drops significantly in 2018–2019, while most companies have good profitability. Therefore, this research aims to test whether profitability always has a positive relationship with the company stock returns. This research uses a sample of 35 IDX Consumer Goods Industry companies for 2017–2019 with a multiple regression method. Profitability variables used in this research are net income, return on equity, and sales growth. The result indicates that net income and return on equity have a significant positive effect on the stock returns; otherwise, sales growth has no significant effect on the stock returns.